The Effect of E-Commerce, Price, and Service Quality on Purchasing Decisions at Mbak Tin Clothing Store in Gudo Market, Jombang Regency - Darma, Poppyatin Eka; Damayanti, Susi (Universitas Nusantara PGRI Kediri, 2025)
Research aim : As a researcher, this article aimed to understand and analyze the effect of e-commerce, price, and service quality on purchasing decisions at Mbak Tin Clothing Store in Gudo Market, Jombang Regency. Design/Method/Approach : These studies use a quantitative method with a causality type. The population in our study included all consumers at Mbak Tin Clothing Store in Gudo Market, the number of which was infinite or uncountable. A sample using this study was 40 respondents selected using a random sample method or by chance (accidental sampling). The method of data collection was through questionnaires. The data gathered was analyzed using the classical assumption test, multiple linear regression analysis, coefficient of determination test, and hypothesis testing using SPSS 23. Research Finding : The results showed that e-commerce, price, and service quality had a significant impact on purchasing decisions at Mbak Tin Clothing Store in Gudo Market, Jombang Regency. Theoretical contribution/Originality : This research focuses on a deeper understanding of how e-commerce, price, and service quality mutually influence consumer decisions when buying. By exploring the relationship between these three factors, this research seeks to understand how the interactions among variables can shape consumer preferences and influence their choices in making purchasing decisions. Practitionel/Policy implication : As a practical, this study could be a practical guidelines for Mbak Tin Clothing Store in Gudo Market to improve consumer purchasing decisions. Research limitation : A limitation of this study is that it was only conducted at Mbak Tin Clothing Store in Gudo Market, the results may not be fully applicable to clothing stores outside traditional markets or outside jombang district.